2005
DOI: 10.2460/javma.2005.226.240
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic responses to West Nile virus in vaccinated and clinically affected horses

Abstract: A portion of horses vaccinated against WNV may respond poorly. Vaccination every 6 months may be indicated in certain horses and in areas of high vector activity. Other preventative methods such as mosquito control are warranted to prevent WNV infection in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 10 publications
3
54
0
1
Order By: Relevance
“…Furthermore, although several studies have noted that some horses vaccinated against WNV respond poorly and that WND can occur in vaccinated animals [2,10,15,25,26], there are no reliable estimates as to the frequency of this phenomenon. The objective of the study reported here was to compare the incidence and effects of natural WNV infection in unvaccinated and vaccinated horses in California.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although several studies have noted that some horses vaccinated against WNV respond poorly and that WND can occur in vaccinated animals [2,10,15,25,26], there are no reliable estimates as to the frequency of this phenomenon. The objective of the study reported here was to compare the incidence and effects of natural WNV infection in unvaccinated and vaccinated horses in California.…”
Section: Introductionmentioning
confidence: 99%
“…Horses are exposed to numerous mosquito bites and may serve as sensitive sentinels for local arbovirus activity, which can be detected by screening for the novel production of specific virus-reactive antibodies ("seroconversion"). Horses infected with WNV may develop neurologic disease, sometimes leading to death, but most infections are subclinical and will only be detected through testing for seroconversion (Davidson et al 2005).…”
mentioning
confidence: 99%
“…Vaccines against WNV and Japanese encephalitis virus are available commercially to horse owners in some countries and the use of these vaccines results in seroconversion (Davidson et al 2005, Hirota et al 2010). …”
mentioning
confidence: 99%
“…Additionally, 3 of the 11 WNV-seropositive horses in this study tested IgM positive, suggesting recent infection. All seropositive horses were asymptomatic but this is not surprising, as a significant proportion of WNV cases present with fever only (Davidson et al 2005), so it is easy to understand how some clinical cases might go unnoticed, misdiagnosed, or remain unreported. In addition to the detection of IgM antibodies, there was no apparent increase in seroprevalence with increased exposure age, also suggesting recent WNV activity in Trinidad.…”
Section: Discussionmentioning
confidence: 99%